Optimization of the Parameters of Different Purification Techniques and Comparison of Their Purification Efficiency and Their Effects on the Metabolic Activity of Adipose Tissue in Autologous Fat Transplantation. Issue 3 (May 2020) - Li, Yilin; Lu, Haibing; Yang, Xiaonan; Jin, Xiaolei; Qi, Zuoliang
Abstract : Abstract: There is still no unified standardized or optimal procedure for lipoaspirate purification and we explored the optimal parameters of 3 purification techniques and compared their efficiencies and effects on the metabolic activity of adipose tissue. The purification efficiency of each technique was compared by analyzing the composition ratio of the processed compounds. The effects of the purification techniques on the dynamic metabolic activity of adipose tissue were evaluated in vitro using the glucose transfer assay. We found that the cotton pad adsorption technique displayed the greatest ability to remove aqueous and oil fractions, followed by centrifugation and sedimentation techniques ( P  < 0.01). The in vitro metabolic activity of adipose tissue peaked at 4 hours. The glucose transfer rates in the cotton pad group and the sedimentation group were significantly higher ( P  < 0.05) than that of the centrifugation group, and the centrifugation method exerted the greatest effect on the metabolic activity of adipose tissue. To sum up, the optimal processing parameters were the following: sedimentation technique, 30 minutes of sedimentation; centrifugation technique, 3 to 5 minutes of centrifugation and centrifugation force of 200 g; and cotton pad adsorption technique, contact area of 5 cm 2 /mL and contact time of 5 minutes. The cotton pad adsorption technique yielded the best purification of the aqueous and oil fractions, followed by the centrifugation technique, whereas the sedimentation technique exhibited the lowest efficiency. The in vitro metabolic activity of adipose tissue peaked at 4 hours, and the cotton pad and sedimentation technique exerted decreased effects on metabolic activity than the centrifugation technique. Abstract : Supplemental Digital Content is available in the text